Visiting Bill and Betty Sanders in Berkeley Hills - Watkins, Howard::::::::: (1980)
Leslie Prusia holding sleepy Katie Rea, Betty Sanders, Bill Sanders, friends, Peggy Sanders wearing white satin blouse, Christine Watkins with white top Console television